Estabelecimento de Panicum maximum e Urochloa brizantha com milho ou soja e cultivo em sucessão de trigo e aveia preta - Mariani, Franciele (2010)
The grain production systems in combination with pastures characterize the crop-livestock systems (CLS) which are generally, more efficient and sustainable. The period after grain harvest of the summer crops coincides with a period of low herbage allowance and low forage nutritive value. The simultaneous establishment of perennial tropical grass forages (PTGF) with grain crops may be an alternative to minimize the fall critical period of herbage allowance, however, must preserve the crop yield and the crop performance in succession. The objective of this study was to propose a new production system to the environmental conditions of northern of Rio Grande do Sul state. The experiment was conducted in two stages, in the summer season corn and soybean was grown with Urochloa brizantha and Panicum maximum. During winter season, in succession were seeded black-oat cultivar Agro Zebu, dual-purpose wheat cultivar BRS Tarumã and wheat cultivar BRS Guamirim. Were evaluated the biomass accumulation, forage nutritive value, crop yield and yield components. In summer, it was observed that the forages intercropped with maize and soybean did not decrease the crop yield, but only the intercropped with maize allowed mechanical harvesting. In winter, BRS Tarumã accumulates more DM and provides more grain yield compared with oat. Summer residues influence the nutritive value and dry matter accumulation of winter cereals, however, the grain yield does not vary. Intercropping summer systems utilizing dual-purpose wheat in the winter season have a higher gross margin. The intercropping of maize and tropical forages can be established to increase herbage allowance after the grain harvest